ISLAM MENGUTAMAKAN ILMU PENGETAHUAN DAN TEKNOLOGI - Yedi Purwanto (Jurnal Sosioteknologi, 2011)
Islam Prioritize to the role of science, technology and art in the advancement of civilization and the Islamic da'wah. Muslims are required to master these three things that can lead to world civilization. This is reflected in a series of revelations received by Prophet Muhammad SAW for the first time that the letter of Al-Alaq paragraphs 1 to 5. Afzalur Rahman in "Muhammad's Encyclopedia of Seerah (1981) said:" The Prophet Muhammad has successfully introduced a new dimension of life order for mankind. His followers were the lovers of true science. They also build a solid foundation for the development of world science, technology, art, and explore the science of God who has never known before. Centuries after the death of his range, they have influenced European culture and civilization. The hadist of Prophet Muhammad elaborates a lot on the importance of science, technology and art for the Muslim future. Keywords: Science, Technology, Art